Pelatihan Digital Marketing Kepada UMKM di Banjar Pitik untuk Daya Saing Usaha - Kadek Novayanti Kusuma Dewi; Luh Putu Mahyuni (Universitas Lancang Kuning, 2022)
Pedungan Village, South Denpasar District is a densely populated village where most of the people depend more on the economy as MSME business actors. From the survey that has been conducted, many MSME players in Banjar Pitik are still taboo in using digital marketing as a marketing medium. Seeing the problems in this situation, it is necessary to hold digital marketing training for MSME players in Banjar Pitik for business competitiveness. The purpose of this community service activity is to help MSMEs in running their businesses so that they can increase sales results as well as business competitiveness. The methods used in collecting this data are observation, interviews, and documentation. The results of this training activity succeeded in reaping positive responses from the participants because in addition to being taught digital marketing training, this activity also succeeded in providing understanding and education on the importance of digital marketing in the era of globalization.